2023
DOI: 10.1097/mou.0000000000001152
|View full text |Cite
|
Sign up to set email alerts
|

Single use flexible ureteroscopes: a review of current technologies and cost effectiveness analysis

Ali Talyshinskii,
Vineet Gauhar,
Daniele Castellani
et al.

Abstract: Purpose of review Flexible ureteroscopy (fURS) has evolved into both diagnostic and therapeutic modalities. Our review discusses the cost-effectiveness of single use flexible ureteroscopes (su-fURS) and the use of these instruments in routine urological practice. Recent findings There are studies which support the use of su-fURS with an argument of both cost and clinical utility over reusable flexible ureteroscopes (ru-fURS). However, the cost may vary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been suggested that su-fURS may be used to preserve ru-fURS in complex urological cases with a high risk of endoscopic injury or fracture. The use of su-fURS may be influenced by the volume of the procedure, the limited availability of sterilization equipment, the durability of ru-fURS, and the potential risk of infectious complications 66 . Adoption of a standardized technology known as ureteroscopic HLL is widespread in the field of urology in China.…”
Section: New Equipment New Technologymentioning
confidence: 99%
“…It has been suggested that su-fURS may be used to preserve ru-fURS in complex urological cases with a high risk of endoscopic injury or fracture. The use of su-fURS may be influenced by the volume of the procedure, the limited availability of sterilization equipment, the durability of ru-fURS, and the potential risk of infectious complications 66 . Adoption of a standardized technology known as ureteroscopic HLL is widespread in the field of urology in China.…”
Section: New Equipment New Technologymentioning
confidence: 99%